SUSTAINABLE DEVELOPMENT AND COMMUNITY PARTICIPATION: A STUDY OF LOCAL GREEN LIVING PROJECTS - Loso Judijanto; Dedah Ningrum; Floribertha Lake (Adisam Publisher, 2026)
This research examines the concept of sustainable development and the role of community participation in the context of Green Living projects at the local level. Given the increasing global concern for environmental issues, the implementation of Green Living projects is often promoted as a potential solution to creating a more sustainable life. This research aims to explore how active community participation can increase the success of such projects and how this approach can be integrated with sustainable development principles. The research results show that direct community involvement in the planning, implementation and evaluation stages of projects plays an important role in achieving positive and sustainable results. Apart from that, community participation has also been proven to increase the level of awareness and shared responsibility in preserving the environment. The conclusion of this research emphasizes that sustainable development not only requires appropriate technical and policy approaches, but also requires active involvement from all levels of society. Therefore, integrating community participation in the design and implementation of Green Living projects is key to achieving sustainable development goals and improving the quality of life of local communities.